EVALUASI HASIL BELAJAR SISWA SMA KRISTEN BARANA’ PADA PEMBELAJARAN TATAP MUKA DI MASA NEW NORMAL - Mirian Tandi; Mesta Limbong (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2021)
The purpose of this study is to evaluate the learning outcomes of Barana Christian High School students' face-to-face learning in the new normal. Face-to-face learning is carried out because many students, parents and teachers complain about learning conducted online from home due to the difficulty of students receiving inadequate learning and networks. This research method uses qualitative method through literature study, observation and problem tree analysis approach with a sample number of 366 students. The results of this study show that the learning objectives have not been achieved due to the decrease in student learning outcomes during this new normal, so it is necessary to increase the interest and motivation of students' learning and teacher skills in supporting the improvement of student learning outcomes. Keywords: evaluation, learning outcomes, face-to-face learning, new normal